In pursuit of a writer from another coast: the literary work of Husein Bašić as a complement to the historical-identity tectonics of Montenegrian-Sandžak Bošnjaks in the critical vision of Elbisa Ustamujić - Spahić, Vedad (Historical Thought, 2025)
Leaving the Bašlar-Begić paradigm of the interpretation of the literary text, which assumes empathy and the conformation of critical consciousness with the world of artwork to the critical and judgmental distance, Elbisa Ustamujić in the monograph on Husein Bašić, establishes an analytical departure from the text using a terminology register in which nowadays it is dominated by the terms such as discourse, difference, cultural memory, identity, intertext (uality), intermediality… Our analysis confirmed the interdisciplinary and methodological adaptability of this critic to the text configurations. Bašić’s novels in Ustamujić’s interpretation appeared as a kind of postcolonial counter-course, “a view from the other side”, from the position of Sandžak-Montenegrin Bosniaks as a politically marginalized nation.